Hubungan Antara Kontrol Diri dengan Kecenderungan Perilaku Narsistik pada Siswi di Smk Negeri 7 Medan - Habibah Tiara AR; Notiva Eryanti; Maghfirah Maghfirah (Jouska: Jurnal Ilmiah Psikologi, 2023)
This article aims to examine the relationship between self-control and the tendency of narcissistic behavior in female students at SMK Negeri 7 Medan. The problem focused on student self-control and narcissistic behavior tendencies. In order to approach this problem, the theoretical reference from Calhoun Acocella (in Ghufron et al., 2011) is used to measure the aspect of self-control and the theory of Raskin et al., (1988) to measure the tendency of narcissistic behavior. The data were collected through a scale and analyzed quantitatively. The number of research samples is 40 students. The data collection technique in this study used purposive sampling. Data collection uses two psychological scales, namely the self-control scale and the narcissistic behavior tendency scale. Based on the results of the data analysis test using the product moment correlation technique (rxy), the result is -0.048 with a significance of p = 0.000 0.050. This study concludes that the hypothesis is accepted, namely that there is a negative relationship between self-control and the tendency of narcissistic behavior in adolescents at SMK Negeri 7 Medan. Self-control is low where the hypothetical mean = 75.5 empirical mean = 65.97 and the difference exceeds the SD number = 10.6. The tendency of narcissistic behavior is high where the hypothetical mean = 80 empirical mean = 107.8 and the difference exceeds the SD number = 13.85. The coefficient of the determinant of the correlation is r2 = 0.301. Self-control provides an effective contribution to the tendency of juvenile delinquency by 30.1%.